2012
DOI: 10.1073/pnas.1201911109
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of the mitotic checkpoint component Mad1 causes chromosomal instability and resistance to microtubule poisons

Abstract: The mitotic checkpoint is the major cell cycle checkpoint acting during mitosis to prevent aneuploidy and chromosomal instability, which are hallmarks of tumor cells. Reduced expression of the mitotic checkpoint component Mad1 causes aneuploidy and promotes tumors in mice [Iwanaga Y, et al. (2007) Cancer Res 67:160–166]. However, the prevalence and consequences of Mad1 overexpression are currently unclear. Here we show that Mad1 is frequently overexpressed in human cancers and that Mad1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 85 publications
(119 reference statements)
4
100
0
Order By: Relevance
“…It has been reported that the weakening of the checkpoint due to individual unattached kinetochores does not block anaphase onset but lead to increased frequency of aneuploidy. 36 In our research, the levels of Mad2 and BubR1 were reduced in EWSR1-depleted cells, but not eliminated, due to the presence of some unaligned chromosomes. We also observed a high ratio of multipolar spindles in EWSR1-depleted cells, which might be the result of weak signal generation at individual unattached kinetochores.…”
Section: Discussionmentioning
confidence: 45%
“…It has been reported that the weakening of the checkpoint due to individual unattached kinetochores does not block anaphase onset but lead to increased frequency of aneuploidy. 36 In our research, the levels of Mad2 and BubR1 were reduced in EWSR1-depleted cells, but not eliminated, due to the presence of some unaligned chromosomes. We also observed a high ratio of multipolar spindles in EWSR1-depleted cells, which might be the result of weak signal generation at individual unattached kinetochores.…”
Section: Discussionmentioning
confidence: 45%
“…This leads to rapid mitotic exit and SAC abolishment. 15,16 Through our study, we hypothesize that reduced Mad1 levels, due to excess miR-125b, increases free-Mad2 pool, which can bind more Cdc20 molecules, as a result of which APC/C remains inactive and cells are halted at metaphase. In summary, (1) the SAC gene MAD1 is a novel target of miR-125b, (2) Mad1 downregulation brings about transient SAC activation and mitotic delay and (3) this delay gives rise to chromosomal abnormalities, presumable accumulation of which leads to apoptosis.…”
Section: Discussionmentioning
confidence: 78%
“…This is reminiscent of a recent report that Mad1 upregulation might promote tumour miR-125b represses MAD1 expression S Bhattacharjya et al formation and manifest resistance to therapies. 16 It is wellknown that accelerated mitotic progression can induce CIN. 29,16 Our data also reveal a higher incidence of chromosomal defects in presence of ectopic miR-125b, mostly in metaphase-to-anaphase transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations